Land Use Change and its Socio-Economic Implications in the Mazahua Area of the Mexican Highlands - López Vazquez, Victor Hugo; Balderas Plata, Miguel Ángel; Chávez Mejía, María Cristina; Juan Pérez, José Isabel; Gutiérrez Cedillo, Jesús Gastón (CIENCIA ergo-sum; Vol. 22 Núm. 2 (2015): CIENCIA ergo-sum (julio-octubre 2015), 2015)
This article shows the land use change between 2000 and 2010 in the Mazahua Region of the State of Mexico and its socio-economic implications. The study is based on the socio-economic geography of Bonfil (1996) and the land use change processes by Fernandez and Prados (2010) to evaluate the land use change. Supervised classification of maximum likelihood and socio-economic and demographic data were used. The results of image analysis were verified on the field. These changes may be explained by population growth, livelihoods dynamics, and the consequent increasing demand for food and housing.